La influencia de la lengua neerlandesa en la zona de Manhattan: Nieuw Amsterdam - Francisco Sánchez Romero (Philologia Hispalensis, 2010)
Everybody knows about New York, Manhattan Island, Hudson River and the largest stock market in the world: Wall Street. But, who settled down first in this city? I mean to offer an approach to the colonization of Manhattan area by the Dutch. I’d also like to talk in depth about the influence of Dutch on American English. Thus, I’m going to build a lexical corpus of Dutch loan- words and loan-translations in English. Subsequently, they will be grouped into semantic fields so that they can be analyzed. Finally, conclusions will be drawn about the most influential semantic field or fields on American English.